Effect of a late afternoon/early evening bout of aerobic exercise on postprandial lipid and lipoprotein particle responses to a high-sugar meal breakfast the following day in postmenopausal women: a randomized cross-over study. Issue 2 (17th January 2022) - Shah, Meena; Gloeckner, Adam; Bailey, Sarah; Adams-Huet, Beverley; Kreutzer, Andreas; Cheek, Dennis; Willis, Jada L; Mitchell, Joel
ABSTRACT: High-sugar consumption is related to dyslipidemia. How acute exercise affects postprandial lipid and lipoprotein particle responses to a high-sugar meal (HSM) in postmenopausal women is unclear. We examined the effects of a late afternoon/early evening bout of aerobic exercise on postprandial lipid and lipoprotein particle responses to a HSM breakfast the following day in 22 postmenopausal women. Subjects underwent exercise (EX) and no exercise (NE) conditions in the evening 13–16 h before the HSM breakfast consumption, in a random order. During the EX condition, subjects performed supervised aerobic exercise for 60 min at 75% of age-predicted maximum heart rate. The HSM (75.6% carbohydrate and 33% energy needs) was consumed after a 12-h fast. Serum lipids and lipoproteins were assessed at baseline and postprandially (60, 120, 180 min). Repeated measures analysis showed significantly lower area under the curve (geometric means [95% CI]) for triglycerides (TG) (2.96[2.43, 3.61] vs. 3.24[2.70, 3.88] mmol/L*hr; p = 0.049) and very low density lipoprotein particles (VLDLP) (114.6[88.2, 148.9] vs. 134.3[108.1, 166.9] nmol/L*hr; p = 0.02) during the EX versus NE condition. There were no condition effects for other variables. In conclusion, the EX versus NE condition lowered postprandial AUC for TG and VLDLP following HSM consumption in postmenopausal women. Trial Registration : ClinicalTrials.gov Identifier: NCT02919488